Funds of Local Government Units in Regional Operational Programmes 2007-2013 and 2014-2020 - Pietrowski Wojciech (Studia Ekonomiczne i Regionalne, 2022)
Subject and purpose of work: The article concerns own contribution of local government units involved in the Regional Operational Programmes. The aim of the research is to assess the amount of own funds in the projects implemented under the ROP.